EU Bioeconomy Economics and Policies: Volume I - Dries, Liesbeth; Heijman, Wim; Jongeneel, Roel; Purnhagen, Kai; Wesseler, Justus (Palgrave Advances in Bioeconomy: Economics and Policies, 2019)
XIII, 234 p. 13 illus., 12 illus. in color.